Attack of malicious objects in computer network under antivirus and quarantine defence - Singha, Anjani Kumar (IJRDO -Journal of Computer Science Engineering, 2017)
Here we develop an epidemic model in a computer network under quarantine and antivirus treatment. Effect of antivirus in the computer network prevents rapidly the spreading behaviour of malicious objects and the role of Quarantine treatment in a computer network increases recovery rate of the infectious computers. The stability of the model and basic reproduction number ( R0 V ) of the model is also derived. Moreover, the effect of antivirus and quarantine in the system is analyzed. MATLAB is employed to solve and simulate the dV        system of equations. S The( simulated)V resultsVI help us to dt understand the spread and control of malicious objects in a computer networkdI dt .  SI   VI  (    ) I I